Teaching english through stories: a meaningful and fun way for children to learn the language (2010)
This article presents the results of a study on utilizing stories for teaching English as a foreign language to children in first, second and third grades. It was carried out in a Colombian public elementary school in Bucaramanga, Colombia. The proposal was initiated by a group of student-teachers at Universidad Cooperativa de Colombia, Seccional Bucaramanga. During the research process the student-teachers were required to plan the course syllabus, create their own stories according to the children’s interests and likes, plan the lessons, and collect and analyze data. Although the student-teachers worked in different grade levels, the results of the study present similarities such as the children’s motivation when the stories were told or read, increased participation in the different activities, comprehension of the stories, and acquisition of the new vocabulary. Key words: Storytelling, story, reading, teaching, children Este artículo presenta los resultados de un estudio sobre el uso de historias para la enseñanza del inglés a niños en los grados primero, segundo y tercero. El estudio se llevó a cabo en una escuela pública de Bucaramanga, Colombia. La propuesta fue iniciada por un grupo de docentes en formación de la Universidad Cooperativa de Colombia, seccional Bucaramanga. Durante el proceso de investigación los docentes elaboraron e implementaron una propuesta de intervención, y además recolectaron y analizaron datos. Aunque los docentes trabajaron en diferentes grados, los resultados del estudio presentaron similitudes, tales como gran motivación de los niños al escuchar o leer las historias, alta participación en las diferentes actividades, comprensión de las historias y adquisición de vocabulario. Palabras clave: narración de historias, lectura de historia, enseñanza a niños